Maqāṣid al-Sharīʿah and Family Resilience: Exploring the Concept of Wasāʾil in Jamaluddin ʿAṭhiyyah’s Thought - Mirwan, Mirwan (Journal of Islamic Thought and Philosophy, 2025)
This study aims to explore Jamaluddin 'Athiyyah's concept of maqāshid al-sharīʿah, focusing on the hierarchical levels of dhārūriyāt, ḥājiyyāt, and taḥsīniyyāt as instrumental means (wasāil) to achieve the ultimate objectives of Shariah within the context of Muslim family resilience. Using a qualitative approach through literature review, this research primarily utilizes 'Athiyyah's Nahwa Taf'il as the primary source. The findings indicate that 'Athiyyah's reinterpretation of maqāshid al-sharīʿah offers an adaptive and dynamic approach to contemporary family challenges such as value degradation and family disintegration. The application of this concept includes the fulfillment of interconnected physical, psychological, and spiritual needs, and character education as instrumental aspects. This study concludes that 'Athiyyah's thought provides a comprehensive and effective conceptual framework for building resilient, balanced, and sustainable Muslim families grounded in Islamic values.